2001
DOI: 10.1136/heart.85.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in heart failure with Cheyne-Stokes respiration

Abstract: Objectives-To document the degree of cognitive impairment in stable heart failure, and to determine its relation to the presence of Cheyne-Stokes respiration during sleep. Subjects-104 heart failure patients and 21 healthy normal volunteers. Methods-Overnight oximetry was used (previously validated as a screening tool for Cheyne-Stokes respiration in heart failure). Cognitive function was assessed using a battery of neuropsychological tests. Left ventricular function was assessed by echocardiography. Results-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Sleeprelated breathing disorders, including obstructive sleep apnea and Cheyne-Stokes respiration with central sleep apnea commonly occur in patients with severe congestive heart failure [24,25], and may be modified by exercise training [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sleeprelated breathing disorders, including obstructive sleep apnea and Cheyne-Stokes respiration with central sleep apnea commonly occur in patients with severe congestive heart failure [24,25], and may be modified by exercise training [26].…”
Section: Discussionmentioning
confidence: 99%
“…80 However, others have found no associations between SDB and selfreported physical function, 31,69 fatigue, 31 or 6-minute walk. 41,81 Sleep efficiency, measured through wrist actigraphy, was associated with both self-reported and actigraph-recorded physical function, 15 and selfreported sleep quality and duration of nocturnal awakenings were associated with 6-minute walk distance in systolic HF patients; self-reported sleep difficulty was also associated with quality of life in older HF patients. 13 However, Erickson and colleagues 16 found that only napping and not feeling tired at bedtime, not nocturnal characteristics, were associated with 6-minute walk distance.…”
Section: Potential Contributions Of Sleep Disturbance To Self-carementioning
confidence: 97%
“…Cognitive impairment in adult patients with CHF, especially in the domains of vigilance and memory, is well described and appears to be reversible with cardiac transplantation. 11,12 Anatomic changes in brain gray matter volume in adults with chronic heart failure have also been reported. 6 Data in children, however, are limited.…”
Section: Heart Failure That Is Medically Managed Disorders Of Myocytementioning
confidence: 93%